Perbedaan hasil belajar kimia siswa yang dibelajarkan dengan media kahoot dan media powerpoint pada materilaju reaksi di SMA - Sari, Aisyah Fitria; Pasar Maulim Silitonga (ARKA INSTITUTE, 2022)
This study aims to determine the comparison of student learning outcomes who are taught using Kahoot learning media and student learning outcomes who are taught using Powerpoint learning media. The population in this study were all students of class XI IPA at Al-Hikmah Private High School in the odd semester of the 2021/2022 academic year. The class sample is a saturated sample and The sample of students was taken purposively 25 students from each class were relatively homogeneous. The research design used was a Pretest-posttest control group design. The instrument used is a test instrument in the form of multiple choice questions related to the reaction rate material. Based on the research results obtained by the right-hand side t test of one sample group, it was found that tcount > ttable is 3.68 > 1.711, meaning that the average student learning outcomes taught by the application of Kahoot learning media are higher than the minimum completeness criteria. The results of further research obtained by using the right-hand side t test of two sample groups, it was found that tcount > ttable , namely 2.11 > 1.67, meaning that the average student learning outcomes who were taught by the application of Kahoot learning media were higher than student learning outcomes which is taught with Powerpoint learning media. In this study, it was also found that in students who were taught by the application of the Kahoot learning media, the percentage of students who achieved the minimum completeness criteria was 92%.